Gay Marriage and the Problem of Property - Andrea B. Carroll; Christopher K. Odinet (Washington University Law Review, 2016)
The Supreme Court’s gay marriage decision in Obergefell has been hailed in almost all corners as a milestone in American jurisprudence. From topics as varied as adoption and taxes, a myriad of rights have now descended upon gay couples as a result of the Court’s ruling. In this Commentary, we explore the little discussed downsides of the decision when it comes to the property rights and debts of the spouses. This is particularly important when considering the rights of third parties and their settled expectations in the context of retroactivity, as well the ways in which the Court’s decision may have the undesirable affect of undoing the carefully laid plans of the spouses. We conclude that courts and legislatures have by no means seen the end of the gay marriage debate. Rather, a host of unforeseen collateral issues lies on the horizon.
Keywords: Gay marriage; Obergefell v. Hodges; Same sex marriage; Same sex divorce; Family Law